2022
DOI: 10.3390/ijerph19073842
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Physical Attractiveness Investments: Overlooked Side of Masculinity

Abstract: Background: Public opinion on who performs more beauty-enhancing behaviors (men or women) seems unanimous. Women are often depicted as primarily interested in how they look, opposed to men, who are presumably less focused on their appearance. However, previous studies might have overlooked how masculinity relates to self-modification among men. Methods: We explored this issue in depth by conducting a qualitative Study 1 aimed to establish how men and women enhance their attractiveness (N = 121) and a quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Mealey (307) found that 20% of men ranked “appearance to opposite sex” as their number 1 reason of 7 for their gym workouts and 22% ranked it as their number 2 reason. Strength exercise as an investment strategy for enhancing physical appearance is also reported more by men than women (251). Finally, among male anabolic steroid users, desires to increase muscle mass and strength, to look good, and attract sexual partners are some of the more highly rated motivators for steroid use (88).…”
Section: Reasons For Strength Training Participationmentioning
confidence: 99%
“…Mealey (307) found that 20% of men ranked “appearance to opposite sex” as their number 1 reason of 7 for their gym workouts and 22% ranked it as their number 2 reason. Strength exercise as an investment strategy for enhancing physical appearance is also reported more by men than women (251). Finally, among male anabolic steroid users, desires to increase muscle mass and strength, to look good, and attract sexual partners are some of the more highly rated motivators for steroid use (88).…”
Section: Reasons For Strength Training Participationmentioning
confidence: 99%
“…As such, the lack of sex differences found in the current study suggests that these theories, and their predicted associations with mental health, are equally relevant to boys and men. This is supported by the recent findings that there are no sex differences in the amount of time men and women invest in enhancing their attractiveness (Kowal & Sorokowski, 2022 ), and the increased rates of body disturbance, steroid use, and eating disorders in boys and young men (Nagata et al, 2020 ).…”
Section: Discussionmentioning
confidence: 69%
“…This suggests that males should be more concerned than females about their attractiveness to mating partners. This potential contradiction may be resolved by a small study that showed no sex differences in desire for personal attractiveness [53]. Because personal physical attractiveness should theoretically be important to mating alliances, we included it here.…”
Section: Alliances That That Support Survival or Reproductionmentioning
confidence: 99%